Kajian terhadap Malaysia Tourism Center (MTC) sebagai pusat penerangan pelancongan dengan melihat maklumbalas di kalangan agensi pelancongan - Jamari, Hazlin (2007)
Tourist Information Center play an important role in tourism marketing. Tourism marketing has two components. The first is advertising and promoting to bring visitors here, and the second is to take care of them while they are here, to encourage them to stay longer, to see other parts of the Country, and to return. Currently, as constituted, Malaysia Tourism Center (MTC) is handling both functions. The purposes of this study were to determine (a) good characteristics for tourist information center in the context of Malaysia, (b) the roles of MTC to travel agency, (c)issues/problems faced by MTC and travel agency in built up good relationships, and (d) to make recommendations for improving MTC services. Based on these specific objectives, the study aimed to have the opinions from key informants through an interview survey obtained from the travel agencies and MTC. Major findings include: (a) â€œproper and strategic locationâ€?, â€œinformationsâ€?, â€œservices/facilitiesâ€?, and â€œattractionsâ€? were recognized as the good characteristics for tourist information center, (b) the roles of MTC to travel agencies identified by key informants of travel agencies and MTC were categorized by two roles: the first is as an information center, and the second is promotion, and (c) â€œlack of good cooperationâ€?, â€œ the unclear roles and objectives of MTCâ€?, â€œlack of informationâ€?, and â€œlack of promotionâ€? were recognized as the issues/problems faced by key informants of MTC and travel agencies. The findings of the studies may contribute to the tourism industry in general. The outcomes of the study identified competencies that would serve as the basis toward developing an effective role of MTC as tourism information center that can improve MTC. In addition, tourists and tour operators would benefit from the improved services offered by the MTC.